Prabowo’s dialogue with Six Editors-in-Chief as a political marketing strategy: A preliminary evaluation using social exchange theory - Eben Ezer Siadari (Privietlab, 2026)
The dialogue between President Prabowo and six leading media editors-in-chief (Dialog Presiden Prabowo Menjawab, PPM Dialogue) as a political communication and Prabowo’s political marketing strategy can be seen as an exchange of resources between Prabowo as an actor in the government’s political market arena and the editors-in-chief as actors in the media’s political market arena. This study conducted a preliminary evaluation of dialogue as political marketing using the Social Exchange Theory framework and political communication concepts. This study found that the exchange of resources took place under conditions of flexible and dynamic agreements, with the power to determine the greater terms resting with Prabowo. Both actors expressed satisfaction with the ongoing exchange, although public evaluations indicated that there were still aspects that needed to be improved. The greater imbalance gained by both actors in the exchange compared to the costs incurred indicates that the Dialog PPM as political marketing has succeeded in achieving its objectives. Therefore, the prospect of continuing open dialogue in the future is promising.